2022
DOI: 10.3389/fmicb.2022.801892
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Species Associated With Human Inflammatory Bowel Disease and Their Pathogenic Mechanisms

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory condition of the gastrointestinal tract with unknown etiology. The pathogenesis of IBD results from immune responses to microbes in the gastrointestinal tract. Various bacterial species that are associated with human IBD have been identified. However, the microbes that trigger the development of human IBD are still not clear. Here we review bacterial species that are associated with human IBD and their pathogenic mechanisms to provide an updated broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 119 publications
(151 reference statements)
1
31
0
Order By: Relevance
“…Although some strains of B.fragilis (e.g., enterotoxigenic B.fragilis ) are enteric pathogens [ 122 ], other commensal strains detected on the inflamed colonic mucosa of CD and UC paediatric patients produce surface immunomodulatory capsular polysaccharide A (PSA) [ 123 ], which has been found in vitro to increase cytokine IL-10 production, inhibit LPS-induced monocyte TNF-α, and induce CD39 + Foxp3 + T regs in a DC-dependent manner [ 124 ]. It has been shown that B.fragilis with a PSA on foetal enterocytes inhibits IL-1β-induced IL-8 production by binding to the TLR2 receptor on CD4 lymphocytes to promote the proliferation of FOXP3 + T regs cells, resulting in increased IL-10 production [ 125 ].…”
Section: Gut Microbiota-derived Scfas As Therapeutic Potential Agents...mentioning
confidence: 99%
“…Although some strains of B.fragilis (e.g., enterotoxigenic B.fragilis ) are enteric pathogens [ 122 ], other commensal strains detected on the inflamed colonic mucosa of CD and UC paediatric patients produce surface immunomodulatory capsular polysaccharide A (PSA) [ 123 ], which has been found in vitro to increase cytokine IL-10 production, inhibit LPS-induced monocyte TNF-α, and induce CD39 + Foxp3 + T regs in a DC-dependent manner [ 124 ]. It has been shown that B.fragilis with a PSA on foetal enterocytes inhibits IL-1β-induced IL-8 production by binding to the TLR2 receptor on CD4 lymphocytes to promote the proliferation of FOXP3 + T regs cells, resulting in increased IL-10 production [ 125 ].…”
Section: Gut Microbiota-derived Scfas As Therapeutic Potential Agents...mentioning
confidence: 99%
“…In addition, several species of GM in pathological contexts are related to increased oxidative stress and inflammation [37]. Increased abundance of several bacteria species such as Enterotoxigenic B. fragilis, Fusobacterium varium, Adherent-invasive Escherichia coli, Campylobacter concisus, and Fusobacterium nucleatum is linked with inflammatory diseases such as inflammatory bowel disease (IBD) and metabolic-associated fat liver disease (MAFLD), respectively [38][39][40][41]. Oxidative stress-mediated by the human microbiome occurs through its ability to alter the cellular ROS by modulating mitochondrial activity [42].…”
Section: The Possible Crosstalk Between Gut Microbiota and Telomere L...mentioning
confidence: 99%
“…Other possible pathogens in the exacerbation of the IBD disease are Mycobacterium avium subspecies paratuberculosis, Clostridium difficile, Listeria monocytogenes, and Campylobacter concisus, as well as viruses, including cytomegalovirus, Epstein-Barr virus, and measles virus [17,81]. In addition, a number of pathogenic parasites may involve in the progression of this disease.…”
Section: Ibd and Gut Microbiotamentioning
confidence: 99%
“…In addition, a number of pathogenic parasites may involve in the progression of this disease. Overexposure of immune system in the presence of too many bacterial materials could also cause the loss of immunological tolerance to the bacteria, which are generally considered the normal flora in the gut [81]. Some of the individual bacterial species that associate with human IBD are reviewed here.…”
Section: Ibd and Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation